Unraveling the β-AMYLOID clearance by astrocytes: Involvement of metabotropic glutamate receptor 3, sAPPα, and class-A scavenger receptor - Durand, Daniela Elizabeth (2019)
The mechanics of β-amyloid (Aβ) clearance by astrocytes has not been univocally described, with different mediators appearing to contribute to this process under different conditions. Our laboratory has demonstrated neuroprotective effects of astroglial subtype 3 metabotropic glutamate receptor (mGlu3R), which are dependent on the secreted form of the amyloid precursor protein (sAPPα) as well as on Aβ clearance; however, the mechanism underlying mGlu3R-induced Aβ uptake by astrocytes remains unclear. The present study shows that conditioned medium from mGlu3R-stimulated astrocytes increased Aβ uptake by naïve astrocytes through a mechanism dependent on sAPPα, since sAPPα depletion from conditioned medium inhibited Aβ phagocytosis. Concordantly, recombinant sAPPα also increased Aβ uptake. Since we show that both sAPPα and the mGlu3R agonist LY379268 increased expression of class-A scavenger receptor (SR-A) in astrocytes, we next determined whether SR-A mediates mGlu3R- or sAPPα-induced Aβ uptake by using astrocyte cultures derived from SR-A knockout mice. We found that the effects of LY379268 as well as sAPPα on Aβ uptake were abolished in SR-A-deficient astrocytes, indicating a major role for this scavenger receptor in LY379268- and sAPPα-stimulated Aβ clearance by astrocytes. We also show results of coimmunoprecipitation and functional assays offering evidence of possible heterotrimerization of sAPPα with Aβ and SR-A which could allow Aβ to enter the astrocyte. In conclusion the present paper describes a novel pathway for Aβ clearance by astrocytes involving sAPPα as an enhancer of SR-A-dependent Aβ phagocytosis.